A novel vascularized patch enhances cell survival and modifies ventricular remodeling in a rat myocardial infarction model - Zhou, Qi; Zhou, Jian-Ye; Zheng, Zhe; Zhang, Hao; Hu, Sheng-Shou (The Journal of thoracic and cardiovascular surgery, 2010)
Although stem cells hold a great therapeutic potential for injured tissues, limited survival of transplanted stem cells has hindered the clinical application of this technology. We hypothesized that an omentum-based stem cell–supporting patch could provide adequate nutrients and microenvironment to prolong cell survival. We examined this hypothesis in rats with experimental myocardial infarction. The omentum-based supporting patch was constructed by stitching polylactic acid-co-glycolic acid polymer seeded with mesenchymal stem cells from male Sprague–Dawley rats. Eight weeks after the experimental myocardial infarction, which was created by ligating the left coronary artery of female Sprague–Dawley rats, mesenchymal stem cells were transplanted with (n = 16) or without (n = 14) the supporting patch. After 4 weeks, transplanted mesenchymal stem cell survival, ventricular remodeling, and cardiac performance were examined. Significantly more cells survived after 4 weeks in rats transplanted with mesenchymal stem cells on the supporting patch assessed by means of polymerase chain reaction detection of the Sry gene than seen in those without the supporting patch (2.61 ± 0.40 vs 1.19 ± 0.12, P < .05). Rats with myocardial infarction that received mesenchymal stem cells with the patch also had significantly improved ventricular remodeling and cardiac function than those without the patch. Wrapping infarcted myocardium with omentum alone did not change the myocardial function. The omentum-based cell-supporting patch provided a favorable microenvironment for transplanted mesenchymal stem cell survival, which resulted in favorable ventricular remodeling and restoration of cardiac function in rats with experimental myocardial infarction. Further validation of the technique in human subjects could make mesenchymal stem cell transplantation a viable therapeutic option for patients with cardiac disease.